PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL DAN KOMITE AUDIT TERHADAP KINERJA KEUANGAN - Sumari, Jenita; Malino, Marlina (Jurnal Unicorn ADPERTISI, 2024)
The aim of this study is to assess the impact of audit committees, management ownership, and institutional ownership on the financial performance (ROA) of manufacturing companies that are publicly traded on the Indonesia Stock Exchange. This study employs a quantitative technique, characterized by systematic, preplanned, and well-structured specifications throughout the entire process of developing the research design. by taking a population of 20 manufacturing companies with an observation period of 2019 to 2022, so that a sample of 20 is obtained. 80. The study is based on secondary data sources, notably the company's annual reports, which encompass the balance sheet and profit and loss report. The aforementioned reports were acquired from the website www.idx.co.id. Meanwhile, the data analysis approach includes the utilization of multiple linear regression analysis, hypothesis testing, assessment of normality, detection of multicollinearity, testing for heteroscedasticity, and other descriptive analysis methods. The study found that audit committees had a substantial and favorable impact on the financial performance (ROA) of manufacturing companies listed on the Indonesian Stock Exchange. Although not statistically significant, institutional ownership had a positive influence on financial success. Conversely, the ownership of managers had a beneficial impact on financial performance, but it did not reach statistical significance.